Mean Square Cordial Labeling of Some Cycle Related Graphs - Dhanalakshmi, S.; Parvathi, N. (International Journal of Engineering and Technology, 2018)
In this paper we investigate the Mean square cordial labeling for some cyclic graphs like Helm graph Hp, Closed helm graph CHp, Gear graph Gp, Sunlet graph SLp, Fan graph F1,p and CpÊ˜nK1 Â .Â